An evaluation of turbulence and tile models at server rack level for data centers. (15th May 2019) - Phan, Long; Hu, Beichao; Lin, Cheng-Xian
Abstract: In recent decades, computational tool is popularly used for thermal management of large data centers to meet the high demand of IT services which causes an increase in thermal load density. In this study, an evaluation of various available tile models at different tile-to-rack airflow rate ratios is carefully conducted using experimental data for one single server rack in a dada center laboratory from the available literature. In addition, several turbulence models are thoroughly studied, and recommendations are provided for the most accurate and less time-consuming turbulence models depending on targeting purposes when applying to a single rack model. A proposed composite performance index is introduced and used for evaluating various tile and turbulence models. It is an interesting finding that the zero-equation produces a very decent result when compared to the widely used standard k- ε . As for the tile model investigated, it is found that the body force and modified body force model are the best candidates for tile modelling applications. The use of zero equation with either body force or modified body force tile model yields either an equivalent or better results in terms of time and accuracy compared to the standard k-ε case combined with the same tile models. Highlights: New performance indexes based on time and accuracy are proposed for model assessment. Body force and modified body force tile models are found to the best tile models among several investigated. Zero-equation model reduces the computing time while yielding good accuracy among other turbulence models. The combination of zero-equation model with either body force or modified body force model is preferred.